An Evaluation of the Methodology Textbook of New Theories in Politics (Positivism and Post-Positivism) - Mojtaba Shariati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The variety of methodological studies in the field of politics, the emergence of post-positivism in the modern age, and the conflicts with positivism make clear the importance of criticizing this work. The importance of evaluating this book is also attributed to the fact that this textbook has been used as a resource for political science students at three academic levels. This article is an attempt to provide a framework for reforming it in the future by reviewing one of the most important educational writings in the field of political science methodology and expressing its strengths and weaknesses. The method of critique of the work is citation-analytical, which has been done in the general framework of work presentation, form criticism, and content criticism. The results indicate that the book in question, although it has strengths in its content, has many drawbacks in form. It is mentioned in the form of articulated tables. Methodological explanations of different theories in different sections, printing, and proper layout are the most important content and form advantages of this work. Lack of sufficient and comprehensive attention to some of the new theories, weaknesses in the critical introduction of existing methodologies, and a multitude of typographical errors are the form and content weaknesses of the book.